Manfaat Technology Mobile Health terhadap Peningkatan Penggunaan Kondom pada ODHA (Journal of Telenursing (JOTING), 2025)
This study aims to determine the effect of m-Health technology  intervention on increasing condom use in ODHA. The research method uses a systematic review  approach through several databases, namely Pumed, Proquest, Science Direct, Sage Journals and Taylor and Francis. The process of analyzing articles uses the PRISMA method. The results of the study show that the benefits of using m-Health technology can increase the use of condoms where the use of technology such as smartphone applications, telemedicine, text messages, as interactive and counseling tools so that patients can receive the reminders, education, and support needed to improve their quality of life. In conclusion, the use of m-Health technology provides real benefits and implications for ODHA to increase the use of condoms as one of the efforts to reduce the rate of HIV/AIDS spread. Keywords: HIV/AIDS, Increased Condom Use, Technology m-Health.